Gambaran Pemanfaatan Buku KIA Pada Ibu Hamil - Vinna Aurelia Widiasari; Nur Azizah Indriastuti (Malahayati Nursing Journal, 2025)
ABSTRACT The Maternal and Child Health (KIA) Book is an important media that functions as a guide for pregnant women to monitor their pregnancy and obtain health information. However, its utilization is still not optimal due to various factors such as the mother's knowledge and attitude. This study aims to determine the description of the utilization of the KIA Book in pregnant women in the work area of the Kasihan 1 Bantul Health Center. This study uses a quantitative approach with a descriptive method. The sample consisted of 33 pregnant women who were selected by considering the theory of Baley and Mahmud and a 10% dropout risk. The instrument used was a questionnaire that had been tested for validity and reliability. Data analysis was carried out univariately and bivariately using SPSS version 26.The majority of respondents had a level of utilization of the KIA Book in the "good" category of 63.6%. The results of the frequency distribution showed that most pregnant women routinely read, carry, and use the KIA Book as a guide to care during pregnancy. However, there were still respondents who were in the "less" category, especially in terms of active use such as self-recording and recommended physical activity. Although most pregnant women have utilized the KIA Book well, overall utilization is still not optimal. Increased education and assistance are needed to optimize the role of the KIA Book as a medium for information and monitoring maternal and child health. Keywords: KIA Book, Pregnant Women, Utilization, Pregnancy ABSTRAK Buku Kesehatan Ibu dan Anak (KIA) merupakan media penting yang berfungsi sebagai panduan bagi ibu hamil untuk memantau kehamilan serta memperoleh informasi kesehatan. Namun, pemanfaatannya masih belum optimal karena berbagai faktor seperti pengetahuan dan sikap ibu. Penelitian ini bertujuan untuk mengetahui gambaran pemanfaatan Buku KIA pada ibu hamil di wilayah kerja Puskesmas Kasihan 1 Bantul. Penelitian ini menggunakan pendekatan kuantitatif dengan metode deskriptif. Sampel pada prnrlitian ini berjumlah 33 ibu hamil yang dipilih dengan mempertimbangkan teori Baley dan Mahmud serta risiko dropout 10%. Instrumen yang digunakan adalah kuesioner yang telah diuji validitas dan reliabilitasnya. Analisis data dilakukan secara univariat dengan menggunakan SPSS versi 26. Mayoritas responden memiliki tingkat pemanfaatan buku KIA dalam kategori "baik" sebesar 63,6%. Hasil distribusi frekuensi menunjukkan sebagian besar ibu hamil rutin membaca, membawa, dan menggunakan buku KIA sebagai panduan perawatan selama kehamilan. Namun, masih terdapat responden yang berada pada kategori "kurang", khususnya pada aspek penggunaan aktif seperti pencatatan mandiri dan aktivitas fisik yang direkomendasikan. Meskipun sebagian besar ibu hamil telah memanfaatkan buku KIA dengan baik, pemanfaatan secara menyeluruh masih belum maksimal. Oleh karena itu diperlukan peningkatan edukasi dan pendampingan untuk mengoptimalkan peran Buku KIA sebagai media informasi dan pemantauan kesehatan ibu dan anak. Kata Kunci: Buku KIA, Ibu Hamil, Pemanfaatan, Kehamilan